Magnetohydrodynamic flow and heat transfer of a hybrid nanofluid over a rotating disk by considering Arrhenius energy. (16th February 2021) - Reddy, M Gnaneswara; R, Naveen Kumar; Prasannakumara, B C; Rudraswamy, N G; Ganesh Kumar, K
Abstract: This research work explores the effect of hybrid nanoparticles on the flow over a rotating disk by using an activation energy model. Here, we considered molybdenum disulfide and ferro sulfate as nanoparticles suspended in base fluid water. The magnetic field is pragmatic normal to the hybrid nanofluid flow direction. The derived nonlinear ordinary differential equations are non-dimensionalized and worked out numerically with the help of Maple software by the RKF-45 method. The scientific results for a non-dimensionalized equation are presented for both nanoparticle and hybrid nanoparticle case. Accoutrements of various predominant restrictions on flow and thermal fields are scanned. Computation estimation for friction factor, local Nusselt number and Sherwood number are also executed. Results reveal that the reduction of the heat transfer rate is greater in hybrid nanoparticles when compared to nanoparticles for increasing values of Eckert Number and the thermal field enhances for the enhanced values of volume fraction.